If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(n + 0.3333333333333) = 1.666666666666n + 1 + 0.5n + -0.33333333333 Reorder the terms: 2(0.3333333333333 + n) = 1.666666666666n + 1 + 0.5n + -0.33333333333 (0.3333333333333 * 2 + n * 2) = 1.666666666666n + 1 + 0.5n + -0.33333333333 (0.6666666667 + 2n) = 1.666666666666n + 1 + 0.5n + -0.33333333333 Reorder the terms: 0.6666666667 + 2n = 1 + -0.33333333333 + 1.666666666666n + 0.5n Combine like terms: 1 + -0.33333333333 = 0.66666666667 0.6666666667 + 2n = 0.66666666667 + 1.666666666666n + 0.5n Combine like terms: 1.666666666666n + 0.5n = 2.166666666666n 0.6666666667 + 2n = 0.66666666667 + 2.166666666666n Solving 0.6666666667 + 2n = 0.66666666667 + 2.166666666666n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2.166666666666n' to each side of the equation. 0.6666666667 + 2n + -2.166666666666n = 0.66666666667 + 2.166666666666n + -2.166666666666n Combine like terms: 2n + -2.166666666666n = -0.166666666666n 0.6666666667 + -0.166666666666n = 0.66666666667 + 2.166666666666n + -2.166666666666n Combine like terms: 2.166666666666n + -2.166666666666n = 0.000000000000 0.6666666667 + -0.166666666666n = 0.66666666667 + 0.000000000000 0.6666666667 + -0.166666666666n = 0.66666666667 Add '-0.6666666667' to each side of the equation. 0.6666666667 + -0.6666666667 + -0.166666666666n = 0.66666666667 + -0.6666666667 Combine like terms: 0.6666666667 + -0.6666666667 = 0.0000000000 0.0000000000 + -0.166666666666n = 0.66666666667 + -0.6666666667 -0.166666666666n = 0.66666666667 + -0.6666666667 Combine like terms: 0.66666666667 + -0.6666666667 = -0.00000000003 -0.166666666666n = -0.00000000003 Divide each side by '-0.166666666666'. n = 0.00000000018 Simplifying n = 0.00000000018
| 4(x-2)=2(x-4)+2 | | 3-7y+4=2y+11-7y | | 120(20)=50(x) | | (2(3)-a)(3+b)(3+c)=0 | | x-(3-x+1)=-x-4 | | x-3(-x+1)=-x-4 | | f(x)=1+ln(1+ln(1+ln(1+x))) | | 19-(5m+7)=4+2m-13 | | 60(36)=60(k) | | (2b-1)i+(a+3)=4-8i | | 4t^2-20t-25=0 | | (3x-5)+(12x)=90 | | (3-2i)-(2x+yi)=7+6i | | 3a-10+4a=5a-7 | | 3.7b+7=8.1b-18.4 | | 42(z)=35(28) | | 4+3+-7=4+-7 | | 36(x)=45(32) | | (2x)=(2y-x) | | (3x-5)=(12x) | | C(x)=.6x+30 | | x-3(-x)+1=-x-6 | | 18(5)=7.5(x) | | 10-(3x-5)=11-4x | | 8+3x=132 | | 10x-50=7x-20 | | x-(3-x+1)=-x-6 | | X^2-11x+48=0 | | 11x-8=x | | 0=(-.02x^2)+1.7x+5.1 | | 90+2x-3+4x+11=180 | | 180=(180-(8x+10))+2x+10+x+30 |